Profile of Pedis Gangrene Patients With Type Ii Diabetes Mellitus at Bhayangkara Hospital Kediri Period January 2021 - March 2022 - R. Mohamad Javier; Yuswar Nurullah Sukin; Mochamad Yunus; Mochamad Aleq Sander (Green Publisher Indonesia, 2022)
Gas gangrene is a disease that is identical to the incidence of type 2 diabetes mellitus with the characteristics of muscle necrosis / myonecrosis and is a very deadly infection of the inner soft tissues, often caused by gram-positive bacteria such as Staphylococcus aureus, Clostridium perifingens. Diabetes mellitus is a collection of symptoms caused by disturbances in the balance between carbohydrates, fats and proteins caused by absolute or relative insulin deficiency, causing hyperglycemia and glucosuria. to describe the profile of patients with gas gangrene pedis caused by type II diabetes mellitus obtained from the results of secondary data research at Bhayangkara Hospital Kediri Period January 2021 - March 2022. This study is an observational study (Non Experimental Design) using a cohort retrospective design method. The sample in this study were patients with Gas Gangrene Pedis who were obtained from the patient's medical records in the period January 2021 - March 2022 at Bhayangkara Hospital Kediri with Type II Diabetes Mellitus. Results: Based on the results of the Association Test between Wagner Grade and Gas Therapy, gangrene pedis has a p value of 0.199. The Wagner Grade variable with gas gangrene pedis therapy had an insignificant relationship with debridement measures n = 8 and the most common bacterium was Pseudomonas aeruginosa with n = 4. Patients with gas gangrene pedis who had a history of not routinely controlling because of their DM treatment, there was a high probability of progressive progression. worsening of his condition due to